Memory Compiler Development and Optimization - Khan, Mehzabeen (My University, 2018)
Memory is represented by different views as an example Timing views, Model view, Layout views. For generating memory cell different view is useful. Backend compiler is product which is used to generate memory for various technologies and various specifications. This process is known as cut generation. Two of views, layout view and netlist view are mostly useful. All the technological, architectural and other information are encoded in BE Compiler. GDS file contains the layout information. CDL file contains the schematic information. It means every memory generator configurations have different Backend compiler, but all have a lot of commonly used code. To reduce BE Compiler development time is one aspect of uniBe. To provide single interface for various type of file is also another aspect of uniBE. It supports multiple technology like 28, 14 nm etc. It also Support multiple architecture. User can insert data using single interface. Multiple criteria for compiler are also supported using this product. In uniBe, another major module is „Checker‟, which checks the input template files, developed by ECE engineers, of a technology with all the cut configurations in such a manner that all the errors in files are detected. Data in files are inserted by end user. Technical data can be incorrect. Checker`s functionality is to verify different kind of checks. UniBe must be faster enough and accurate.
Keywords: Compiler; Memory